Pengaruh Price To Book Value, Price Earning Ratio Dan Deviden Yield Terhadap Harga Saham Perusahaan Kontruksi Dan Bangunan Yang Terdaftar Di Bursa Efek Indonesia (Studi Kasus 2014-2018) - Enny Arita (CV. ITTC INDONESIA, 2022)
This study aims to analyze Price to Book Value (PBV), Price Earining Ratio (PER), Dividend Yield (DY) of Building Construction Companies for the period 2014- 2018. The object of research in this study is a building construction company listed on the IDX. This study uses annual data, namely Fact Book 2014,2015,2016,2017,2018. Data analysis method used is a quantitative method. The results showed that the Price to Book Value Variable, Price Earning Ration, Dividend Yield partially (t test) 2 variables had a significant effect and 1 variable had a non-significant effect on the Building Construction Company Stock Price. Simultaneous test results (f) significantly influence the stock prices of construction and building companies